Soluble human leukocyte antigen‐G is a potential embryo viability biomarker and a positive predictor of live‐births in humans. (11th November 2021) - Vani, Venkatappa; Vasan, Satya S.; Adiga, Satish K.; Varsha, Samson Roy; Sachdeva, Geetanjali; Kumar, Pratap; Seshagiri, Polani B.
Abstract: Problem: Human infertility affects 15–20% of reproductive‐age couples and it is mitigated by assisted reproductive technology (ART) approaches. Poor biological viability of embryos contributes to implantation failure and live birth rate (LBR). This study is aimed to examine whether or not embryo‐secreted soluble human leukocyte antigen‐G (sHLA‐G) is (i) associated with developing embryos and (ii) able to predict successful pregnancy outcome. Method of study: A retrospective, multicentric study using 539 human embryo spent medium samples (E‐SMs), analysed for sHLA‐G levels by ELISA. Correlation analysis was performed on sHLA‐G levels with developing embryonic stages, their quality scores and pregnancy outcome in terms of LBR. Results: Of 539 E‐SMs analysed, 445 had detectable sHLA‐G (83%) with levels varying within and across clinics and, between stages of embryonic development. Levels of sHLA‐G (ng/mL) were significantly ( P < .05) different in E‐SMs of cleavage‐stage embryos versus blastocysts. There was an insignificant correlation between the sHLA‐G levels and morphology scores of embryos. But, sHLA‐G levels showed a positive correlation with grades of blastocysts and importantly, its levels were significantly ( P < .05) higher in live‐birth vis‐a‐vis no‐birth cases. Also, levels were higher in live‐births out of blastocysts‐ETs versus cleavage‐stage‐embryo transfers. Altered levels were observed with embryos, which resulted in miscarriages. Overall, a significant ( P < .0001) association of sHLA‐G with live births was observed. Conclusion: Embryo‐derived sHLA‐G can be a valuable embryo viability, independent, biomarker, which can predict live‐birth outcome and it could be useful as an adjunct to existing criteria for elective single embryo transfer.